Analysis of interaction of agricultural (AE) and processing enterprises (PE) of the AIC on the basis of cost flow models in the steady regime - V. I. Loyko; T. P. Baranovskaya (Новые технологии)
In the first article on the topic the basic concepts and statements of the theory of cost flow models were studied and both a scheme of commodity-money circulation and a schematic diagram of the studied economic chain were developed. This article presents the results of a study of the steady regime of the turnover chain of the costs of interacting agricultural and processing enterprises.